The Reinforcement Learning Workshop : Learn How to Apply Cutting-Edge Reinforcement Learning Algorithms to a Wide Range of Control Problems. - Palmas, Alessandro (Packt Publishing, Limited, 2020)
With the help of practical examples and engaging activities, The Reinforcement Learning Workshop takes you through reinforcement learning's core techniques and frameworks. Following a hands-on approach, it allows you to learn reinforcement learning at your own pace to develop your own intelligent applications with ease.
Description based upon print version of record.
Batch Normalization.
Keywords: Reinforcement learning.; Algorithms.; Algorithms; Apprentissage par renforcement (Intelligence artificielle); Algorithmes.; algorithms.; Programming & scripting languages: general.; Artificial intelligence.; Neural networks & fuzzy systems.; Computers -- Intelligence (AI) & Semantics.; Computers -- Neural Networks.; Computers -- Programming Languages -- Python.; Reinforcement learning